Bioinspired synthesis and activity characterization of iron oxide nanoparticles made using Rhamnus Triquetra leaf extract. (10th January 2020) - Abbasi, Banzeer Ahsan; Iqbal, Javed; Zahra, Syeda Anber; Shahbaz, Amir; Kanwal, Sobia; Rabbani, Atiya; Mahmood, Tariq
Abstract: The present study reports a facile, green, low cost and ecofriendly route for the formation of IONPs using Rhamnus triquetra (RT) leaves extract. The color change of the reaction mixture from dark brown to reddish black determined the formation of IONPs which was further confirmed by the presence of an absorbance peak at 300 nm. The IONPs were further characterized using various characterization techniques; SEM, TEM, XRD, DLS, FT-IR, EDX and Raman. The bioactive functional groups available in the leaves extract of RT involved in reduction and stabilization of IONPs were determined by FTIR analysis. The IONPs were further evaluated for anticancer activity against HepG2 cancer cells (IC50 : 11.2 μ g ml −1 ). Dose-dependent cytotoxicity assays were performed against Leishmanial amastigotes (IC50 : 25.09 μ g ml −1 ) and promastigotes (IC50 : 11.54 μ g ml −1 ). Additionally, cytotoxicity assay was determined against brine shrimps (IC50 : 35.37 μ g ml −1 ). Disc-diffusion method displayed significant antibacterial and antifungal activities. Significant antioxidants and enzyme inhibition potentials were revealed. The biocompatibility tests were done against human RBCs and macrophages. Overall, IONPs are non-toxic and shown potential role in multiple biological application. We hope, that the present study could be a helpful contribution and will open new avenues for diverse fields including drug design, pharmaceutical and biomedical industries.